A brief summary of the Ordovician conodont faunas from the Iberian Peninsula - Sarmiento, Graciela N.; Gutiérrez-Marco, J. C.; Rodríguez-Cañero, R.; Martín Algarra, A.; Navas-Parejo, P. (CSIC - Instituto Geológico y Minero de España (IGME), 2011)
Ordovician conodont studies in the Iberian Peninsula were initiated by Fuganti and Serpagli (1968), who recognized 21 morphospecies included in 15 morphogenera in the Upper Ordovician Urbana Limestone from a single locality in the Central Iberian Zone. Two years later Boersma (in Hartevelt, 1970) identified several morphotaxa in the Upper Ordovician Estana Formation of the Central Pyrenees. In the type section of the Upper Ordovician Cystoid Limestone of the Eastern Iberian Cordillera, Carls (1975) recognised 31 conodont morphotaxa. These pioneer findings were followed by the contributions of Kolb (1978), Hafenrichter (1979), Robert (1980), Robardet (1982) and Sanz (1988), who increased the number of taxa and localities with Katian conodonts, mostly attributed to the Amorphognathus ordovicicus Zone. For twenty years, our knowledge on Ordovician conodonts came only from the single ubiquitous limestone unit that occurs in the upper part of many Iberian successions. Nonetheless, these are predominantly composed of terrigenous rocks (shales, siltstones and sandstones) which were deposited at high Gondwanan paleolatitudes near the South Pole (Gutiérrez-Marco et al., 2002, 2004). Then, some of these clastic deposits (siltstones, shales and storm-induced coquinoid lenses, sometimes calcareous) were also sampled for conodonts: while siltstones and shales produced only fragmentary specimens, bioclastic beds in tempestites yielded usually fragmentary, but recognisable, elements. Peer reviewed